Filleting of Fish and Utilization of Filleting Waste. - PERIGREEN, P A; NAIR, A LEKSHMY; PRABHU, P V (Fishery Technology, 2017)
A manual method of filleting of different varieties of fishes, yields of skin-on and skinless fillets that can be obtained from them, levels of recovery of picked meat from the filleting waste and the utilization of the latter for the production of fish mealhave been reported in this communication. The compositions of meal thus preparedare also given.